On Square-Integrable Representations of A Lie Group of 4-Dimensional Standard Filiform Lie Algebra - Kurniadi, Edi (CAUCHY, 2020)
In this paper, we study irreducible unitary representations of a real standard filiform Lie group with dimension equals 4 with respect to its basis. To find this representations we apply the orbit method introduced by Kirillov. The corresponding orbit of this representation is genereric orbits of dimension 2. Furthermore, we show that obtained representation of this group is square-integrable. Moreover, in such case , we shall consider its Duflo-Moore operator as multiple of scalarÂ  identity operator. In our case Â that scalar is equal to one.